2019
DOI: 10.1038/s41598-019-55215-6
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence angiography for pre-treatment assessment and treatment monitoring following photodynamic therapy: a basal cell carcinoma patient study

Abstract: Microvascular networks of human basal cell carcinomas (Bcc) and surrounding skin were assessed with optical coherence angiography (ocA) in conjunction with photodynamic therapy (pDt). ocA images were collected and analyzed in 31 lesions pre-treatment, and immediately/24 hours/3-12 months posttreatment. Pre-treatment OCA enabled differentiation between prevalent subtypes of BCC (nodular and superficial) and nodular-with-necrotic-core BCC subtypes with a diagnostic accuracy of 78%; this can facilitate more accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…For the first time we applied in combination OCA and OCE to test the ability these optical methods to in vivo predict tumor response. Another goal of the study was to estimate the universality of these approaches by applying each of these methods to another type of tumor and another type of therapy in comparison with previous, partially similar, applications of OCA and OCE [5,6,19,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the first time we applied in combination OCA and OCE to test the ability these optical methods to in vivo predict tumor response. Another goal of the study was to estimate the universality of these approaches by applying each of these methods to another type of tumor and another type of therapy in comparison with previous, partially similar, applications of OCA and OCE [5,6,19,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Among the methods of detection, visualization and quantitative assessment/monitoring of tumor microcirculation (perfusion) OCT-based angiography (OCA) has demonstrated high potential [5,6,[14][15][16][17][18]. Recently, observation of blood-circulation blockages in tumors and in peri-tumorous regions based on OCA has proven to be very useful for accurate prediction of the outcome of vasculature-targeted PDT during the first 24 hours post-PDT on experimental animals [5,6] and patients [19], as well as for detection of side effects of radio-therapy manifested via microvasculature alterations in the oral cavity [16]. However, unlike the fairly easily observed perturbation in the microcirculation of blood, the assessment of the histological structure of tissues lacks precise, non-invasive methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the OCE method may be also useful in combination with subsequent conventional histology to facilitate the recognition of areas in the tissue with changes that may be missed during routine microscopic examination. A more complete assessment of the tumor response and thereby the effectiveness of treatment can be achieved by combining OCE with other modalities based on the same OCT setup (angiography 67,68 , polarization-sensitive OCT 5 , estimation of the optical-signal decay 69 , etc.). www.nature.com/scientificreports/ Knowing both the advantages and the limitations of the OCE method (first of all, limited depth of scanning typical of OCT), it can be concluded that the method can be valuable in the study of surface structures (skin and mucous, where a biopsy is limited or not advisable) and the effects of various destructive or therapeutic/cosmetic agents on them.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the OCE method may be also useful in combination with subsequent conventional histology to facilitate the recognition of areas in the tissue with changes that may be missed during routine microscopic examination. A more complete assessment of the tumor response and thereby the effectiveness of treatment can be achieved by combining OCE with other modalities based on the same OCT setup (angiography 67 , 68 , polarization-sensitive OCT 5 , estimation of the optical-signal decay 69 , etc.).…”
Section: Discussionmentioning
confidence: 99%